WITHDRAWAL OF VENTILATION AT THE PATIENT'S REQUEST IN MND: DOCTORS VIEWS ON THE ETHICAL CHALLENGES INVOLVED. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Faull, Christina; Phelps, Kay; Regen, Emma; Rowe-Haynes, Cassy; Oliver, David; McDermott, Christopher
Abstract : Background: Little is known about the withdrawal of NIV at the request of a patient. The NICE guidance on the use of NIV in MND (2010) identifies the lack of any clarity in how this process should be managed. NICE specifically suggests interviewing the professionals involved as a focus of research. Aims: To explore the ethical issues that arise for doctors who have been involved in the withdrawal of NIV at the request of a patient with MND. Methods: A retrospective qualitative interview study of 20 Doctors including specialists in palliative care, respiratory, neurology and general practice. Results: Participants were clear that patients have the right to withdrawal from treatment and it would be unethical to continue treatment. Despite this clarity, withdrawal of NIV where the result will be death in a short timescale, can feel challenging. In such cases doctors may feel the need for a second opinion and affirmation that withdrawal of ventilation is ethically sound. The challenge is augmented by the need for the doctor to spend considerable time discussing the ethics of each case with colleagues and family members. Even when doctors feel the ethics are clear there can be an underlying fear that colleagues and the public will not see it this way, and a fear that they will be seen as assisting death. Many doctors had experienced disagreement from colleagues who felt that assisting patients in their request and managing the consequent symptoms, was unethical. Conclusions: Though the ethics of withdrawal of treatment at the patient's request are clear, in a situation where the result will be immediate death it feels ethically challenging for many doctors. Open ethical discussions of these situations and written guidance on the ethics of withdrawal of NIV in MND would alleviate many doctors fears.